2011
DOI: 10.1016/j.exger.2010.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Obesity-mediated inflammatory microenvironment stimulates osteoclastogenesis and bone loss in mice

Abstract: Clinical evidence indicates that fat is inversely proportional to bone mass in elderly obese women. However, it remains unclear whether obesity accelerates bone loss. In this report we present evidence that increased visceral fat leads to inflammation and subsequent bone loss in 12-monthold C57BL/6J mice that were fed 10% corn oil (CO)-based diet and a control lab chow (LC) for 6 months. As expected from our previous work, CO-fed mice demonstrated increased visceral fat and enhanced total body fat mass compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
129
3
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(142 citation statements)
references
References 62 publications
9
129
3
1
Order By: Relevance
“…9,43 Consistent with these studies, our results showed that the HF diet induced significantly higher TNF-a and IL-6 concentrations in serum along with a trend toward elevated TRACP. TRACP is an osteoclastic bone resorption marker that has been reported to increase in mice fed a HF diet.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…9,43 Consistent with these studies, our results showed that the HF diet induced significantly higher TNF-a and IL-6 concentrations in serum along with a trend toward elevated TRACP. TRACP is an osteoclastic bone resorption marker that has been reported to increase in mice fed a HF diet.…”
Section: Discussionsupporting
confidence: 80%
“…7,8 The potential mechanisms may involve the abundant adipokines and pro-inflammatory cytokines produced by adipose tissue, which can regulate bone metabolism. [9][10][11] Furthermore, marrow adipogenesis may be inversely related to osteoblastogenesis, 12,13 since adipocytes and bone-forming osteoblasts are derived from a common multipotential mesenchymal stem cell.…”
Section: Introductionmentioning
confidence: 99%
“…However, an increasing number of studies have indicated that obesity in female mice is accompanied by bone loss (8,(13)(14)(15). This may be due to the role of adipose tissue as an endocrine organ, secreting pro-inflammatory cytokines, whose effects damage the trabecular bone (16). Therefore, the use of different mouse models in prevous studies may explain these inconsistencies.…”
Section: Discussionmentioning
confidence: 90%
“…Following this, adipocyte-secreted cytokines affected the OPG/RANKL/RANK trail system, resulting in a marked increase in osteoclast differentiation. Halade et al (16) reported that OPG secretion decreased and RANKL expression increased in osteoblasts stimulated with adipocyte-secreted factors. By contrast, Goto et al (20) demonstrated that adipocyte-secreted cytokines upregulated RANKL mRNA expression in osteoblasts, consistent with osteoclast differentiation in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, these fracture sites [7] differ from the fracture sites most commonly seen in osteoporosis, which are the wrist, upper arm, rib, hip and spine [7]. A number of possible contributors to compromised skeletal health in obesity have been proposed, including but not limited to reduced vitamin D bioavailability [9,14] and an inflammatory state that increases bone breakdown [15]. Moreover, individuals with obesity have a heightened risk of mobility impairment [16] and falls [17,18], due to factors such as poor compensatory stepping responses and postural instability [17] as well as intramuscular fat infiltration which reduces muscle strength [9,19,20].…”
Section: Introductionmentioning
confidence: 99%